الحياة الفكرية والثقافية في عهد الموحدين: تلمسان أنموذجا - بلعباس، نجاة; مرتاض، محمد (مركز البصيرة للبحوث والاستشارات والخدمات التعلمية, 2015)
This research aims to identify the most important merits of the cultural and intellectual life at the time of the monotheists who continued the march of progress and uphold the dissemination of Islam and science. their period is the most fertile period of the Middle Ages, thanks to what they have achieved progress and prosperity of the intellectual and scientific in various types of science and knowledge Tlemcen was one of the most important science centers in the monotheists land, it contributed effectively in providing the intellectual movement and establishing the principle of civilizational and cultural communication between the west Islam.
يهدف هذا البحث إلى تبيان أهم مكونات الحياة الثقافية والفكرية على عهد الموحدين الذين واصلوا مسيرة التقدم وأعلاء شأن المغرب الإسلامي ونشر الدين والعلم، فشهد حكمهم فترة من أخصب الفت ا رت إبان العصور الوسطى، وبفضل ما وصلوا إليه من تقدم وازدهار فكري وعلمي في شتى أنواع العلوم والمعارف، وكانت تلمسان واحدة من أهم مراكز العلم في الدولة الموحدية تسهم بشكل فعال في رفد الحركة الفكرية، وترسيخ مبدأ التواصل الحضاري والثقافي بين أصقاع المغرب الإسلامي.
Keywords: تاريخ الجزائر -- الدولة الموحدية -- المغرب الإسلامي -- المدن الجزائرية -- مدينة تلمسان